Critique on Salafibism and it’s Significance for Indonesian Islamic Moderation: Study on Khaled Abou El-Fadhl’s Thought - Fanani, Muhyar; Iswanto, Bambang (Mazahib, 2023)
This paper aims to prove the importance of Khaled Abou el-Fadhl's (b. 1963) critique on Salafibism for mainstreaming Islamic moderation in contemporary Indonesia. This research examines Khaled's critique using the approach of ‘ilm uṣūl al-fiqh, a technique that analyzes the nature, secrets, and purposes of Islamic teachings including its laws. The problem examined in this research is the significance of Khaled's critique on Salafibism for mainstreaming Islamic moderation in contemporary Indonesia. This research concludes that from the perspective of ‘ilm uṣūl al-fiqh, Khaled's critique on Salafibism is crucial for mainstreaming Islamic modernization in present-day Indonesia. The significance of the critique lies in three things: (1). Providing the new awareness and energy for Indonesian Islamic scholars to campaign for moderate Islam and rejects puritanical Islam, especially Salafibism. (2). It provides theoretical guidance for the Islamic moderation movement in Indonesia, especially the importance of the balance between literalism and maqāṣid as well as between text and context in understanding the holy book. (3). Creating the practical guidance for the Islamic moderation movement in Indonesia to counter extremism. This research indicates that adopting a moderate approach to Islam holds significant promise for achieving local, national, and global religious harmony. In contrast, the puritanical approach, which hinders such concord, should be abandoned. Keywords: Critique, puritanism, salafibism, Islamic moderation, contemporary Indonesia